THE EFFECT OF USSD POP-UP NOTIFICATION ADVERTISING ON INTERESTS IN BUYING SME’s PRODUCTS - Erina Sovania; Annathasia Puji Erasashanti (UNIVERSITAS INDRAPRASTA PGRI, 2020)
Hard to imagine if now living without a cellphone. All information can be provided quickly and instantly via mobile. Advertisements on mobile phones are becoming the current trend and target by advertisers despite the high possibility of recipients seeing and responding to the ads that appear. This study intends to measure whether the mobile USSD Pop-up Notification advertisement has an influence and relationship on consumer buying interest. The research method used is a descriptive quantitative method by collecting data through questionnaires to 385 respondents. The data analysis technique used is correlation analysis and simple linear regression. The results of the correlation coefficient test obtained the number 0.63 where the interpretation produced shows the existence of a Strong Relationship, and coefficient determination of 40%, means a contribution of the variable USSD Pop-up Notification advertising can provide buying interest of 40%, while the remaining 60% is influenced by other variables not examined in this study. For hypothesis testing, it can be seen that the t value is 15.951 with a significance value of 0.000 <0.05 which means there is a Significant Effect between variable X on variable Y. Finally, the study found that USSD Pop-up Notification advertising has a significant positive impact on consumer buying interest